Empathic Cultural Mapping: Little data, big data, knowledge transfer and exchange. (2018) - Goopy, Suzanne; Turin, Tanvir; Kassan, Anusha; O'Brien, Mary; McCormack, Gavin; Chapman, Jonathan; Charania, Irina; Ferreira, Carla; Silversides, Halley
No abstract available